2019
DOI: 10.3386/w26519
|View full text |Cite
|
Sign up to set email alerts
|

Labor in the Boardroom

Abstract: We estimate the wage effects of shared governance, or codetermination, in the form of a mandate of one third of corporate board seats going to worker representatives. We study a reformin Germany that abruptly abolished this mandate for stock corporations incorporated after August 1994, while it locked the mandate for the slightly older cohorts. Our research design compares firm cohorts incorporated before the reform and after; in a robustness check we additionally draw on the analogous difference in unaffected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 82 publications
(74 reference statements)
3
71
1
Order By: Relevance
“…Of course, other attributes also vary with establishment size so our analysis of worker codetermination and establishment size does not definitively pin down only variation in codetermination. See Jäger and Schoefer (2019) for more evidence on the effects of codetermination in the related context of Germany. 1981) and Bewley (2002) and potentially consistent with our alternative non-Coasean framework described in Section 5.…”
Section: C3 Detailed Discussion: Results Of Complier Analysismentioning
confidence: 99%
“…Of course, other attributes also vary with establishment size so our analysis of worker codetermination and establishment size does not definitively pin down only variation in codetermination. See Jäger and Schoefer (2019) for more evidence on the effects of codetermination in the related context of Germany. 1981) and Bewley (2002) and potentially consistent with our alternative non-Coasean framework described in Section 5.…”
Section: C3 Detailed Discussion: Results Of Complier Analysismentioning
confidence: 99%
“…In the German context, workers' representation on boards is referred to as "shared governance" or "codetermination" (Jäger et al 2019). Robert Schols and Sigurt Vitols found that in Germany, union representation on boards pos-itively aligns with substantive CSR, like "emissions reduction, the publication of a CSR report and commitment to employment security, " but not with symbolic CSR, like being a signatory to the UN Global Compact (Scholz and Vitols 2019: 244).…”
Section: Csr and Transnational Labor Activism: Two Disconnected Fi Eldsmentioning
confidence: 99%
“…While one might suggest that these sorts of firms that make power distribution more equitable among workers and management might generate efficiency costs, existing evidence suggests that, if anything, more democratically structured firms are often times more productive than their less democratic counter-parts (Blasi, Freeman, and Kruse 2014;Jager, Schoefer, and Heining 2019). If these firms are not less efficient than their less democratic counterparts (private corporations for instance), then is it the case that we don't observe workplace democratization because Americans simply don't want to work at these types of firms?…”
mentioning
confidence: 99%
“…For sociological work, seeFligstein (1993),Davis and Thompson (1994),Davis and Greve (1997),Kang and Sorenson (1999), andGoldstein (2012). For economics work, seeHart and Moore (1990),Rajan and Zingales (1998),La Porta, Lopez-de-Silanes, and Shleifer (1999),La Porta et al (2000),Rajan and Zingales (2002),Gompers, Ishii, and Metrick (2003),Pagano and Volpin (2005),Blasi, Freeman, and Kruse (2014),Azar, Schmalz, and Tecu (2018),Jager, Schoefer, and Heining (2019),and Ederer, Cunningham, and Ma (Forthcoming). For an exception to this in political science, seeCioffi and Hopner (2006),Ciepley (2013Ciepley ( , 2017, Hertel-Fernandez (2018), and Hertel-Fernandez, Kimball, and Kochan (2019) for instance.…”
mentioning
confidence: 99%